Insights into the active sites of dual‐zone synergistic catalysts for semi‐hydrogenation under hydrogen spillover. Issue 3 (14th September 2022) - Wang, Shuai; Lv, Yipin; Wang, Xilong; Gao, Daowei; Duan, Aijun; Zhao, Huaiqing; Zheng, Peng; Chen, Guozhu
Abstract: A well‐defined catalyst with platinum (Pt) and gold (Au) encapsulated in micropore and mesopore of micro‐mesoporous zeolite (Pt‐Au/TMSN), respectively, was designed to investigate the original active sites of semi‐hydrogenation. Specifically, hydrogen molecules are dissociated on Pt nanoclusters (NCs) to form hydrogen atoms that migrate to the surfaces of TMSN zeolite and Au nanoparticles (NPs) through hydrogen spillover effect. The characterization and catalytic results demonstrate that the Au NPs and zeolite surface are both identified as the semi‐hydrogenation sites. Especially, the Au active site with low adsorption ability of alkene possesses preferable selectivity in the semi‐hydrogenation of phenylacetylene and 1, 5‐cyclooctadiene. Noteworthy, the Pt‐Au/TMSN exhibits higher selectivity of phenylethylene and cyclooctene than Pt/TMSN, as well as higher turnover frequency than Au/MSN. This work creates an effective regulation strategy of active sites working with a tandem mechanism for improving the semi‐hydrogenation performance.